2020
DOI: 10.1002/celc.201901818
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic PtBi Nanoplates with High Catalytic Activity towards Electro‐oxidation of Formic Acid and Glycerol

Abstract: Despite considerable progress made for direct liquid fuel cells, developing efficient electrocatalysts for the oxidation of small organic molecules reaction remains a challenge. Herein, we employed a facile one‐pot method to synthesize hexagonal intermetallic PtBi nanoplates. Benefiting from the unique structure and third body effect, the mass activity of formic acid oxidation on PtBi/C at peak potential reaches 9.06 A ⋅ mgPt−1, which is 10.4 times higher than that of commercial Pt/C catalyst, making it the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…. PtBi/C was found to have 3.2 times higher mass activity compared to Pt/C for glycerol oxidation in alkaline media [21]. Polycrystalline Pt−Bi catalysts demonstrated a five fold activity increase compared to polycrystalline Pt catalyst [22].…”
Section: Resultsmentioning
confidence: 99%
“…. PtBi/C was found to have 3.2 times higher mass activity compared to Pt/C for glycerol oxidation in alkaline media [21]. Polycrystalline Pt−Bi catalysts demonstrated a five fold activity increase compared to polycrystalline Pt catalyst [22].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the in situ FTIR can be used to fleetly detect the key intermediates during reaction processes, which is conducive to investigate the reaction mechanism and propose the corresponding reaction pathway. [ 29,30 ]…”
Section: Electrochemical Conversion Of Glycerolmentioning
confidence: 99%
“…Coutanceau et al investigated the influence of introduced Bi on the GOR performance of carbon‐supported or unsupported Pt, Pd, and PtPd alloy nanoparticles in alkaline media by combining cyclic voltammograms and in situ FTIR. [ 58 ] They found that Bi adatoms did not bring much improvement on the catalytic activity of non‐supported Pd nanospheres toward GOR, but greatly enhanced the reactivity of carbon‐supported Pd x Bi 10− x /C, Pt 9 Bi 1 /C, and Pd 4.5 Pt 4.5 Bi 1 /C catalysts. Moreover, they also found that the introduced Bi had no influence on the selectivity of Pd, but significantly affected the selectivity of Pt containing catalysts at low potential.…”
Section: Electrocatalystsmentioning
confidence: 99%
“…The greatest dissolution features were observed when the experiments were performed in a CO-saturated electrolyte implying that the indirect oxidation pathway (i.e., through CO adsorption and oxidation) plays a key role in formate electrooxidation using PtRu as the catalyst. Other Pt-based alloys have been tested in formic acid/formate electrooxidation such as PtFe [79], PtAu [67,90], PtAg [65], PtCo [66], PtCu [68], PdPt [39,71,73,91,92], PtBi [69,93] or PtSn [68,93,94] (Table 2). Indeed, the use of Bi, Sb, As, Pb, Sn and Ge as dopants for Pt has been investigated from several decades ago, finding optimum loadings of around 50% in most cases [93,94].…”
Section: Bimetallic and Trimetallic Pt-based Catalystsmentioning
confidence: 99%